Searching for the safest abdominal closure technique after emergency laparotomy for Hinchey III and IV peritonitis - Tamini, Nicolo; Cereda, Marco; Capelli, Giulia; Giani, Alessandro; Gianotti, Luca (International Surgery Journal, 2017)
Background: The optimal strategy for abdominal wall closure has been an ongoing issue of debate and convincing evidence is still lacking. The INLINE systematic review and meta-analysis published on annals of surgery 2010 suggested that a running suture with a slowly absorbable suture material was the gold standard technique for abdominal wall closure after elective surgery, while there’s no general agreement in the emergency setting. Methods: Retrospective study regarding patients who underwent emergency surgery for a generalized peritonitis due to colonic perforation from 2002 to 2014 at San Gerardo hospital (Monza, Italy). Particularly study analyzed differences between continuous suture (Maxon loop, Covidien ©) and interrupted suture (Safil, B. Braun ©) for fascial closure and between metallic clips and second intention healing for incision management. After completion of data retrieval, 110 patients were included in the statistical analysis. Results: Incisional hernia rate was 15/101 (14.9%) and surgical site infection rate was 29/110 (26.4%). No significant statistical differences were found between incidence of incisional hernia and surgical site infection in the two groups, although there was a higher prevalence of incisional hernia in the running suture group (25% vs 11,7%). There was no difference between skin-stapler’s and second-intention’s wound closure groups in terms of surgical site infection and incisional hernia development. Conclusions: We consider reasonable to use an interrupted long time absorbable suture for fascial closure after emergency midline laparotomy for Hinchey III and IV peritonitis, at least in high-risk patients. Considering skin closure, suggestion is to perform a primary skin closure.